Heterogeneous Copper(I)-Catalyzed Cascade Addition–Oxidative Cyclization of Nitriles with 2-Aminopyridines or Amidines: Efficient and Practical Synthesis of 1,2,4-Triazoles - Xia, Jianhui; Huang, Xue; Cai, Mingzhong (Synthesis, 2019)
The heterogeneous cascade addition-oxidative cyclization of nitriles with 2-aminopyridines or amidines was achieved in 1,2-dichlorobenzene or DMSO at 120–130 °C by using a 1,10-phenanthroline-functionalized MCM-41-supported copper(I) complex [Phen-MCM-41-CuBr] as the catalyst and air as the oxidant. The approach was used to generate a wide variety of 1,2,4-triazole derivatives in mostly high yields. This heterogeneous copper(I) catalyst could be easily prepared in a two-step procedure from commercially or readily available and inexpensive reagents and it exhibited higher catalytic activity than the CuBr/1,10-Phen system. Phen-MCM-41-CuBr was also easy to recover and was recyclable up to eight times with almost consistent activity.
Keywords: copper; 1,2,4-triazole; oxidative cyclization; heterogeneous catalysis; cascade reaction